Binding of omeprazole to protein targets identified by monoclonal antibodies - Naw May Pearl Cartee (PLoS ONE, 2020)
Omeprazole is the most commonly used proton pump inhibitor (PPI), a class of medications whose therapeutic mechanism of action involves formation of a disulfide linkage to cysteine residues in the H+/K+ ATPase pump on gastric secretory cells. Covalent linkage between the sole sulfur group of omeprazole and selected cysteine residues of the pump protein results in inhibition of acid secretion in the stomach, an effect that ameliorates gastroesophageal reflux and peptic ulcer disease. PPIs, though useful for specific conditions when used transiently, are associated with diverse untoward effects when used long term. The mechanisms underlying these potential off-target effects remain unclear. PPIs may, in fact, interact with non-canonical target proteins (non-pump molecules) resulting in unexpected pathophysiological effects, but few studies describe off-target PPI binding. Here, we describe successful cloning of monoclonal antibodies against protein-bound omeprazole. We developed and used monoclonal antibodies to characterize the protein target range of omeprazole, stability of omeprazole-bound proteins, and the involvement of cysteines in binding of omeprazole to targets. We demonstrate that a wide range of diverse proteins are targeted by omeprazole. Protein complexes, detected by Western blotting, are resistant to heat, detergents, and reducing agents. Reaction of omeprazole occurs with cysteine-free proteins, is not fully inhibited by cysteine alkylation, occurs at neutral pH, and induces protein multimerization. At least two other clinically used PPIs, rabeprazole and tenatoprazole, are capable of binding to proteins in a similar fashion. We conclude that omeprazole binds to multiple proteins and is capable of forming highly stable complexes that are not dependent on disulfide linkages between the drug and protein targets. Further studies made possible by these antibodies may shed light on whether PPI-protein complexes underlie off-target untoward effects of chronic PPI use.